INVESTIGATING THE EFFECT AND STUDENTS' PERCEPTIONS OF USING INSTAGRAM AS A WRITING TEACHING TOOL IN INDONESIAN EFL CLASSROOMS - Siti Melasari; Bela Ayu Permatasari; Afnal Lazuardi; Naf’an Tarihoran (Adisam Publisher, 2026)
This study aims to investigate the effect of using Instagram as a writing teaching tool and to explore students’ perceptions of its implementation in Indonesian EFL classrooms. A quantitative research design employing a survey method was utilized, involving undergraduate students from the English Education Department at UIN Sultan Maulana Hasanuddin Banten. Data were collected through a structured questionnaire distributed via Google Forms and analyzed using descriptive statistics, including percentages and mean scores. The findings indicate that Instagram has a positive effect on students’ writing learning, particularly in enhancing writing practice and engagement. Furthermore, students’ perceptions toward the use of Instagram fall into a moderate to high category, suggesting that the platform is considered a useful and supportive learning tool. Aspects such as motivation, interaction, and engagement were also identified as contributing factors in supporting the writing learning process. However, the effectiveness of Instagram largely depends on its pedagogical integration within the classroom.